Assessment of Internal Jugular Vein Size in Healthy Subjects with Magnetic Resonance and Semiautomatic Processing. (29th February 2016) - Laganà, M. M.; Pelizzari, L.; Scaccianoce, E.; Dipasquale, O.; Ricci, C.; Baglio, F.; Cecconi, P.; Baselli, G.
Abstract : Background and Objectives . The hypothesized link between extracranial venous abnormalities and some neurological disorders awoke interest in the investigation of the internal jugular veins (IJVs). However, different IJV cross-sectional area (CSA) values are currently reported in literature. In this study, we introduced a semiautomatic method to measure and normalize the CSA and the degree of circularity (Circ) of IJVs along their whole length. Methods . Thirty-six healthy subjects (31.22 ± 9.29 years) were recruited and the 2D time-of-flight magnetic resonance venography was acquired with a 1.5 T Siemens scanner. The IJV were segmented on an axial slice, the contours were propagated in 3D. Then, IJV CSA and Circ were computed between the first and the seventh cervical levels (C1–C7) and normalized among subjects. Inter- and intrarater repeatability were assessed. Results . IJV CSA and Circ were significantly different among cervical levels (p < 0.001 ). A trend for side difference was observed for CSA (larger right IJV, p = 0.06 ), but not for Circ (p = 0.5 ). Excellent inter- and intrarater repeatability was obtained for all the measures. Conclusion . This study proposed a reliable semiautomatic method able to measure the IJV area and shape along C1–C7, and suitable for defining the normality thresholds for future clinical studies.